O forno cerâmico da Correlhã - Ponte de Lima - Almeida, Carlos A. Brochado de; Antunes, João M. Viana; Sousa, Maria José Carvalho e; Cunha, Rui M. Cavalheiro da (História: revista da Faculdade de Letras da Universidade do Porto, 2019)
.